Pengaruh Model Pembelajaran Berdiferensiasi dan Direct Instruction Terhadap Hasil Belajar Ditinjau dari Minat Siswa - Muhammad Ghazali (STKIP Taman Siswa Bima, 2024)
This study aims to determine the effect of differentiated learning and Direct Instruction models on student learning outcomes, viewed from the perspective of student learning interest. The research was conducted in one of the Elementary Schools in Bima Regency, West Nusa Tenggara Province, using experimental methods and a 2 x 2 by-level research design. The results of the study indicate that: (1) The learning outcomes of students who follow the differentiated learning model are higher compared to those who follow the Direct Instruction model, (2) There is an interaction between the differentiated learning and Direct Instruction models with student learning interest towards learning outcomes, (3) Students with high learning interest perform better in the differentiated learning model compared to the Direct Instruction model, and (4) Students with low learning interest perform better in the Direct Instruction model compared to the differentiated learning model